2021
DOI: 10.3390/ani11102872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pantothenic Acid Supplementation on Growth Performance, Carcass Traits, Plasma Parameters of Starter White Pekin Ducks Fed a Corn–Soybean Meal Diet

Abstract: This study aimed to evaluate the effects of different dietary pantothenic acid levels on growth performance, carcass traits, and plasma biochemical parameters of starter Pekin ducks from 1 to 21 days of age, as well as the pantothenic acid requirement of starter ducks. A total of 384 one-day-old male white Pekin ducklings were assigned randomly into 6 dietary treatments, each with 8 replicate pens of 8 ducks. Ducks were fed conventional basal corn–soybean diets containing 8.5, 10.5, 12.5, 14.5, 16.5, and 18.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Although animal selection promotes significant improvements in growth rates and meat production, a detailed understanding of muscle development is necessary in order to prevent physiological disorders, changes in composition of the muscle fiber type, and metabolic alterations that could influence meat quality ( Deeb and Lamont, 2002 ; Ruusunen and Puolanne, 2004 ; Aliabad et al, 2011 ; Tang et al, 2021 ). Within this context, metabolomics has been used to elucidate the biological mechanisms underlying muscle development related to the production of different bird species ( Wang et al, 2017 ; Ceribeli et al, 2018 ; Cônsolo et al, 2020 ; Ma et al, 2020 ; Basile et al, 2021 ), since metabolites are the intermediate products or end-products of complex cellular reactions and are sensitive markers of physiological activity ( Fontanesi, 2016 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although animal selection promotes significant improvements in growth rates and meat production, a detailed understanding of muscle development is necessary in order to prevent physiological disorders, changes in composition of the muscle fiber type, and metabolic alterations that could influence meat quality ( Deeb and Lamont, 2002 ; Ruusunen and Puolanne, 2004 ; Aliabad et al, 2011 ; Tang et al, 2021 ). Within this context, metabolomics has been used to elucidate the biological mechanisms underlying muscle development related to the production of different bird species ( Wang et al, 2017 ; Ceribeli et al, 2018 ; Cônsolo et al, 2020 ; Ma et al, 2020 ; Basile et al, 2021 ), since metabolites are the intermediate products or end-products of complex cellular reactions and are sensitive markers of physiological activity ( Fontanesi, 2016 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that PA de ciency can result in convulsions, the adrenal gland, anemia, hypoglycemia, hyperventilation and tachycardia were also been impaired [24]. Such as, PA de ciency in poultry could cause fasting hypoglycemia, growth retardation, locomotor abnormalities, and high mortality [25][26][27][28]. Whereas, The PA de ciency in pigs displayed intestinal problems, spastic gait and several species endure nerve demyelination [29].…”
Section: Introductionmentioning
confidence: 99%